2022
DOI: 10.1039/d2ra05943f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the choice of buffer on the electrochemical reduction of Cr(vi) in water on carbon electrodes

Abstract: The nature of the buffer influences the PCET step gating Cr(vi) reduction in water at pH 4.75, as well as the extent of deposition on carbon electrodes. Electrode activity is recovered without polishing, through a simple acid wash step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…An estimate of the rate constant can be obtained from the slope, which here yields k = 4.9 × 10 2 M –1 s –1 (Figure S8). We have previously shown that Cr(VI) reduction in similar conditions is initiated by the transfer of 1e – /1H + . , The electron here is supplied by the catalyst, and the H + is expected to be supplied by the buffer (pH 4 citrate). A solution chemistry report investigating the use of Cr(VI) as a chemical oxidant for Fe(II) at 303 K proposed a rate law which would translate to a rate constant of 8.5 × 10 2 M –1 s –1 in our conditions (see calculation in the SI page SI-8) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An estimate of the rate constant can be obtained from the slope, which here yields k = 4.9 × 10 2 M –1 s –1 (Figure S8). We have previously shown that Cr(VI) reduction in similar conditions is initiated by the transfer of 1e – /1H + . , The electron here is supplied by the catalyst, and the H + is expected to be supplied by the buffer (pH 4 citrate). A solution chemistry report investigating the use of Cr(VI) as a chemical oxidant for Fe(II) at 303 K proposed a rate law which would translate to a rate constant of 8.5 × 10 2 M –1 s –1 in our conditions (see calculation in the SI page SI-8) .…”
Section: Resultsmentioning
confidence: 99%
“…In prior work, we have observed rapid fouling of carbon electrodes in bulk electrolysis conditions, with the presence of Cr(III) confirmed by X-ray photoelectron spectroscopy. 15 Here we report the impact of using a redox mediator as a molecular electrocatalyst S2). An isosbestic point is observed at 466 nm, which further supports the clean reduction of Cr(VI) by [Fe(CN) 6 ] 4− and the generation of [Fe(CN) 6 ] 3− .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations